The Effectiveness of Fun Game Strategy in Improving Children’s Recognition of Geometric Shapes - Hazizah, Nur; Murni, Sri (Journal of Nonformal Education, 2019)
Early childhood is an individual who is developing a process of growth This research is based on the underdeveloped ability of children to identify the geometry of children in the Al-Hidayah Kindergarten of Kamil. This phenomenon is due to the selection and use of inaccurate learning strategies that are not appealing to children. This research aims to help improve children’s recognition of geometric shapes through a fun game. This research used a pre-experimental method using one group pre-test post-test design. The subjects selected were 13 students of TK Al-Hidayah Tilatang Kamang. The data were collected using observation and the data analysis was examined by a statistical test. The descriptive result showed that fun game has improved children’s recognition of geometric shapes. The statistical analysis obtained a significant difference between pre-test and post-test scores. Hence, the fun game strategy has effectively improved children’s recognition of geometric shapes at TK Al-Hidayah Tilatang Kamang.